1969
DOI: 10.1128/jb.100.1.180-186.1969
|View full text |Cite
|
Sign up to set email alerts
|

Acetate Utilization and Macromolecular Synthesis During Sporulation of Yeast

Abstract: Acetate utilization and macromolecule synthesis during sporulation (meiosis) of Saccharomyces cerevisiae were studied. When diploid cells are transferred from glucose nutrient medium to acetate sporulation medium at early stationary phase, respiration of the exogenously supplied acetate proceeds without any apparent lag. At the completion of ascospore development, 62% of the acetate carbon consumed has been respired, 22% remains in the soluble pool, and 16% is incorporated into lipids, protein, nucleic acids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(69 citation statements)
references
References 12 publications
5
64
0
Order By: Relevance
“…Further, we found that energy metabolism is key for this form of mutagenesis. Cells maintained in glucose (a fermentative, glycolytic energy source ( 22 )) acquired mutations most frequently, while cells in acetate (a carbon source that must be utilized by aerobic respiration ( 23 )) had the fewest acquired mutations (see Figure 4C). Moreover, increasing the concentration of glucose from 2% (the amount normally used in media) to 8% led to a five-fold increase in the frequency of mutations (see Figure 4D).…”
Section: Figurementioning
confidence: 99%
“…Further, we found that energy metabolism is key for this form of mutagenesis. Cells maintained in glucose (a fermentative, glycolytic energy source ( 22 )) acquired mutations most frequently, while cells in acetate (a carbon source that must be utilized by aerobic respiration ( 23 )) had the fewest acquired mutations (see Figure 4C). Moreover, increasing the concentration of glucose from 2% (the amount normally used in media) to 8% led to a five-fold increase in the frequency of mutations (see Figure 4D).…”
Section: Figurementioning
confidence: 99%
“…Sporulating cells are known to assimilate acetate by respiration and to produce carbon dioxide (Esposito et al, 1969), which is partly accumulated in medium mainly as bicarbonic ion (HCO 3 ) at pH 7 to 9 (Fowell, 1969). During sporulation of diploid cells at high and low densities, culture a The filtrate was prepared from sporulating culture.…”
Section: Bicarbonate Acts As Mepmentioning
confidence: 99%
“…Despite sharing many common core components, notable contrasts have emerged between the two model yeast systems. There are substantial differences in how these morphologically distinct yeasts regulate the cell cycle, including how cell size is measured, how nutrient conditions regulate mating and meiosis [35][36][37], how the substrate specificity of the CDK is controlled [38][39][40], and how polarity and cytokinesis are regulated by the cell cycle [34]. These variations may not fully capture the variability in mechanisms controlling division.…”
Section: Introductionmentioning
confidence: 99%